Washing away poverty: water, democracy and gendered poverty eradication in South Africa - Schreiner, B.; Mohapi, N.; van Koppen, Barbara (2004)
This article discusses ways in which the South African Government and grassroots organizations envisage and implement democracy achieved since 1994 in the eld of water resources management. The focus is on the democratic, political and economic freedom and equality in resource rights for poor black women, who are central to poverty eradication. While the new water policy and law provide an enabling framework for achieving these goals, implementation on the ground encounters both new opportunities and constraints. This is illustrated by several cases of establishing South Africa’s new water management institutions: catchment management agencies and water user associations. The important nexus between state-led democratization of water resources management and bottom-up grassroots movements is also discussed. The article concludes that the Government’s af rmative and targeted intervention is indispensable for redressing gender inequalities and eradicating poverty.